In vitro investigation of the genotoxicity of portimine, a cyclic imine toxin produced by the dinoflagellate Vulcanodinium rugosum, on human hepatic HepaRG cells. (June 2021) - Hogeveen, Kevin; Huet, Sylvie; Besnard, Charlène; Murray, J. Sam; Harwood, D. Tim; Selwood, Andy I.; Fessard, Valérie
Abstract: Portimine, a recently identified cyclic imine produced by the dinoflagellate Vulcanodinium rugosum, has been described as a potent apoptotic agent in contrast to most of the cyclic imines that are well-known to be neurological toxins. As apoptosis can be a consequence of a high level of DNA lesions, we investigated the responses of portimine on several endpoints aimed at detecting DNA damage in the hepatic cell line HepaRG. Portimine induced phosphorylation of H2AX, which could possibly be consistent with the previously published induction of apoptosis with this toxin. In addition, detection of apoptosis through the activation of caspase-3, the induction of strand breaks detected by the comet assay as well as chromosome and genome mutations using the micronucleus assay were addressed. Surprisingly, portimine treatment resulted in increases in only γH2AX in differentiated HepaRG cells whereas no effects on the other endpoints were detected. These increases in γH2AX in the absence of genotoxic effects in the other tests could indicate that portimine could possibly induce a DNA replication stress and/or that the compound can be detoxified by the HepaRG cells. Highlights: In contrast to results from other cell lines, portimine did not induce apoptosis in HepaRG cells. Portimine induced γH2AX in HepaRG cells, but no DNA damage in the comet assay. Portimine was not mutagenic in the micronucleus assay on HepaRG cells. Portimine could possibly induce a DNA replication stress.